Composition for preparing zirconium oxide ceramic, zirconium oxide ceramic and preparation method thereof, and electronic product housing

By controlling the content of specific elements and secondary phases in zirconia ceramics, a tetragonal zirconia-yttrium oxide solid solution is formed, which solves the shortcomings of zirconia ceramics in terms of impact resistance, density, dielectric constant and processability, and realizes low-cost and high-efficiency ceramic preparation.

CN116535207BActive Publication Date: 2025-01-14BYD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210096030.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-26
Publication Date
2025-01-14
Estimated Expiration
2042-01-26

AI Technical Summary

Technical Problem

Existing zirconia ceramics have limitations in manufacturing large-area exterior parts. They have weak impact resistance, semi-permeability leading to increased costs, high density resulting in heavy weight, high dielectric constant affecting signal transmission, and high processing difficulty, resulting in low yield.

Method used

By limiting the content range and composition of specific elements in zirconia ceramics, and adding SrAl12O19 and SrAl2O4 secondary phases, a solid solution of tetragonal zirconia and yttrium oxide is formed, thereby optimizing the hardness, density, dielectric constant, light transmittance and processability of zirconia ceramics.

Benefits of technology

It achieves low hardness, low density, low dielectric constant, high toughness, low light transmittance, and easy processing, meeting the needs of electronic product casings in the 5G era, reducing production costs and improving yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003491028640000171
    Figure BDA0003491028640000171
  • Figure BDA0003491028640000181
    Figure BDA0003491028640000181
  • Figure BDA0003491028640000191
    Figure BDA0003491028640000191
Patent Text Reader

Abstract

The present invention relates to the technical field of zirconia ceramics, and in particular to a composition for preparing zirconia ceramics, a zirconia ceramic and a preparation method thereof, and an electronic product housing. Based on the total amount of the zirconia ceramic, the zirconia ceramic contains, in terms of elements: 20.65-45.43wt% of Zr, 0.61-3.43wt% of Y, 4.53-29.83wt% of Sr, and 5.05-31.69wt% of Al; and the zirconia ceramic includes: 30-63wt% of tetragonal zirconia and 37-70wt% of a secondary phase, and the secondary phase contains SrAl 12 O 19 and / or SrAl2O4; the tetragonal zirconia is a solid solution of yttria and zirconia. The zirconia ceramic provided by the present invention simultaneously satisfies the advantages of low hardness, low density, low dielectric constant, low light transmittance, high impact resistance and easy processing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zirconia ceramics, and in particular to a composition for preparing zirconia ceramics, a zirconia ceramic and a preparation method thereof, and an electronic product housing. Background Art

[0002] Zirconia ceramics are widely used because they have the characteristics of good corrosion resistance, high hardness and high strength of conventional ceramics. Although the toughness of zirconia ceramics (reaching 5-6MPa·m 1 / 2 ) is higher than other conventional ceramics, but when made into large-area appearance parts, it has the disadvantage of weak impact resistance. In addition, when prepared as a mobile phone back cover product, due to its thin thickness, the semi-permeability of the zirconia ceramic itself will be magnified, so it is necessary to introduce a process of coating ink on the back to prevent the internal components from being seen, thereby increasing the cost; in addition, the high density brings about a large weight problem, and the high dielectric constant brings about a signal transmission problem. In response to these problems, some manufacturers reduce the density and dielectric constant by adding more alumina, but the high hardness and high brittleness of alumina will lead to a significant increase in processing difficulty, resulting in low yield and high cost, making production impossible. Therefore, a ceramic with low hardness, low density, low dielectric constant, low light transmittance, high impact resistance and easy processing has been developed, which has become very important for the application of ceramic back covers in the 5G era. Summary of the invention

[0003] The purpose of the present invention is to overcome the problems that the existing zirconia ceramics cannot have low hardness, low density, low dielectric constant, low light transmittance, high impact resistance and easy processing at the same time, and provide a composition for preparing zirconia ceramics, a zirconia ceramic and a preparation method thereof, and an electronic product housing. The zirconia ceramics limit the content range and composition of specific elements so that the zirconia ceramics meet the characteristics of low density, low dielectric constant, high toughness, low light transmittance, high impact resistance and easy processing while meeting the requirements of low hardness.

[0004] In order to achieve the above-mentioned object, the first aspect of the present invention provides a zirconia ceramic, based on the total amount of the zirconia ceramic, the zirconia ceramic comprises, in terms of elements: 20.65-45.43wt% Zr, 0.61-3.43wt% Y, 4.53-29.83wt% Sr and 5.05-31.69wt% Al; and the zirconia ceramic comprises: 30-63wt% tetragonal zirconia and 37-70wt% secondary phase, and the secondary phase comprises SrAl 12 O 19 and / or SrAl2O4; the tetragonal zirconia is a solid solution of yttria and zirconium oxide.

[0005] Preferably, in the zirconia ceramic, SrAl 12 O 19 It exists in the form of whiskers, and SrAl2O4 exists in the form of spinel.

[0006] Preferably, based on the total amount of the zirconia ceramic, the zirconia ceramic contains, in terms of elements: 27.53-43.26wt% Zr, 0.81-3.27wt% Y, 4.88-25.56wt% Sr and 10.49-27.16wt% Al; the zirconia ceramic includes: 40-60wt% tetragonal zirconia and 40-60wt% secondary phase.

[0007] The second aspect of the present invention provides a composition for preparing the zirconia ceramic provided in the first aspect, the composition comprising: zirconia powder, strontium oxide powder and aluminum oxide powder; wherein, based on the total amount of the zirconia powder, the zirconia powder contains 1.5-4 mol% of yttrium oxide.

[0008] Preferably, based on the total amount of the composition, the content of the zirconium oxide powder is 30-63wt%, preferably 40-60wt%; the content of the strontium oxide powder is 5.35-35.27wt%, preferably 5.78-30.23wt%; the content of the aluminum oxide powder is 18.35-59.86wt%, preferably 19.83-51.31wt%.

[0009] A third aspect of the present invention provides a method for preparing a zirconia ceramic, the method comprising the following steps:

[0010] (1) mixing the powders in the composition provided in the second aspect with water, a dispersant and a binder and wet grinding them to obtain a slurry;

[0011] (2) drying the slurry to obtain composite zirconia ceramic powder;

[0012] (3) The composite zirconia ceramic powder is molded and sintered in sequence to obtain zirconia ceramic.

[0013] Preferably, in step (1), the weight ratio of the dispersant, the binder and the composition is 0.005-0.5:0.5-5:100, preferably 0.01-0.1:2-5:100.

[0014] A fourth aspect of the present invention provides an electronic product housing, wherein the electronic product housing contains the zirconium oxide ceramic provided in the first aspect.

[0015] Through the above technical scheme, the zirconia ceramics provided by the present invention, by limiting the element content and composition in the zirconia ceramics, as well as the synergistic effect of specific elements and specific compositions, make the zirconia ceramics have the characteristics of low density, low dielectric constant, high toughness, low light transmittance, high impact resistance and easy processing under the premise of low hardness. Specifically, the present invention controls "based on the total amount of zirconia ceramics, the zirconia ceramics contain, in terms of elements: 20.65-45.43wt% Zr, 0.61-3.43wt% Y, 4.53-29.83wt% Sr and 5.05-31.69wt% Al" and "the zirconia ceramics include: 30-63wt% tetragonal zirconia and 37-70wt% secondary phase, and the secondary phase contains SrAl 12 O 19 The technical characteristics of "and / or SrAl2O4" and the synergistic effect between the two make the zirconia ceramics meet the following requirements: hardness ≤ 1300Hv; density ≤ 5.15g / cm 3 ; Dielectric constant ≤ 23; Toughness ≥ 4MPa·m 1 / 2 ; Light transmittance (800nm) ≤1.5%; Thinning speed ≥30 wires / h; Average drop hammer height ≥20cm.

[0016] At the same time, the preparation method of the zirconia ceramic provided by the present invention simplifies the process flow and facilitates industrial production under the premise of reducing costs and saving energy. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] The first aspect of the present invention provides a zirconia ceramic, based on the total amount of the zirconia ceramic, the zirconia ceramic comprises, in terms of elements: 20.65-45.43wt% Zr, 0.61-3.43wt% Y, 4.53-29.83wt% Sr and 5.05-31.69wt% Al; and the zirconia ceramic comprises: 30-63wt% tetragonal zirconia and 37-70wt% secondary phase, and the secondary phase comprises SrAl 12 O 19 and / or SrAl2O4; the tetragonal zirconia is a solid solution of yttria and zirconium oxide.

[0019] The present invention limits the molar ratio α of Sr and Al so that the secondary phase contains SrAl12 O 19 Whiskers and / or SrAl2O4 spinel, thereby improving the hardness of zirconia ceramics and making zirconia ceramics have the properties of low density, low dielectric constant, high toughness, low light transmittance, high impact resistance and easy processing.

[0020] In some embodiments of the present invention, preferably, in the zirconia ceramic, when the molar ratio α of Sr to Al satisfies: 1:12<α<1:2, the secondary phase comprises SrAl 12 O 19 and SrAl2O4.

[0021] In some embodiments of the present invention, preferably, in the zirconia ceramic, when the molar ratio α of Sr to Al satisfies: 1:12<α<1:2, based on the total amount of the zirconia ceramic, the zirconia ceramic comprises: 30-63wt% tetragonal zirconia, 18.5-35wt% SrAl 12 O 19 and 18.5-35wt% SrAl2O4.

[0022] In some embodiments of the present invention, preferably, in the zirconia ceramic, when the molar ratio α of Sr to Al satisfies: α=1:12, the secondary phase comprises SrAl 12 O 19 .

[0023] In some embodiments of the present invention, preferably, in the zirconia ceramic, when the molar ratio α of Sr to Al satisfies: α=1:12, based on the total amount of the zirconia ceramic, the zirconia ceramic comprises: 30-63wt% of tetragonal zirconia and 37-70wt% of SrAl 12 O 19 .

[0024] In some embodiments of the present invention, preferably, in the zirconia ceramic, when the molar ratio α of Sr to Al satisfies: α=1:2, the secondary phase comprises SrAl2O4.

[0025] In some embodiments of the present invention, preferably, in the zirconia ceramic, when the molar ratio α of Sr and Al satisfies: α=1:2, based on the total amount of the zirconia ceramic, the zirconia ceramic comprises: 30-63wt% of tetragonal zirconia and 37-70wt% of SrAl2O4.

[0026] In some embodiments of the present invention, preferably, in the zirconia ceramic, SrAl 12 O 19In the present invention, SrAl2O4 exists in the form of whiskers and SrAl2O4 exists in the form of spinel. 12 O 19 Whiskers can improve the mechanical properties of zirconia ceramics; SrAl2O4 spinel can reduce the sintering temperature.

[0027] In some embodiments of the present invention, in order to further take into account the mechanical properties of zirconia ceramics. Preferably, SrAl 12 O 19 The aspect ratio of the whiskers is ≥4:1, preferably 4-7:1.

[0028] In the present invention, the zirconia ceramic may contain other elements, such as O, in addition to Zr, Sr, Y and Al; the sum of all elements contained in the zirconia ceramic is 100wt%.

[0029] In the present invention, unless otherwise specified, the content parameters of each element can be tested by XRF using an energy dispersive X-ray fluorescence spectrometer EDX-7000.

[0030] In the present invention, in order to further make the zirconia ceramic have low hardness, low light transmittance, high toughness, high impact resistance, low density, low dielectric constant and easy processing. Preferably, based on the total amount of the zirconia ceramic, the zirconia ceramic contains, in terms of elements: 27.53-43.26wt% Zr, 0.81-3.27wt% Y, 4.88-25.56wt% Sr and 10.49-27.16wt% Al; the zirconia ceramic includes: 40-60wt% tetragonal zirconia and 40-60wt% secondary phase.

[0031] In the present invention, unless otherwise specified, the content of the phase (e.g., tetragonal zirconia, secondary phase, etc.) in the zirconia ceramic can be determined by XRD. In the XRD spectrum, the diffraction peak of the tetragonal phase of zirconia appears, which may be a solid solution formed by yttrium oxide and zirconia. Preferably, the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconia; further preferably, the content of yttrium oxide in the tetragonal zirconia is 2.6-6.93wt%. The zirconia ceramic may also contain other phases, but they have no negative impact on the zirconia ceramic of the present invention. In the present invention, the above-mentioned content of the phase contained in the zirconia ceramic is based on the zirconia ceramic.

[0032] In some embodiments of the present invention, based on the total amount of the zirconia ceramic, the zirconia ceramic further comprises: 0-0.5 wt % of monoclinic zirconia.

[0033] The zirconia ceramic provided by the present invention has low hardness. Preferably, the zirconia ceramic satisfies: hardness ≤ 1300 Hv, preferably 1050-1290 Hv.

[0034] The zirconia ceramic provided by the present invention has low dielectric constant and low density parameters, achieving lightweight. Preferably, the zirconia ceramic satisfies: dielectric constant ≤ 23, preferably 14-22.5; density ≤ 5.15 g / cm 3 , preferably 4.5-5.1g / cm 3 .

[0035] The zirconia ceramics provided by the present invention meet the following requirements: toughness ≥ 4MPa·m 1 / 2 , preferably 4-6MPa·m 1 / 2 It can be seen that the zirconia ceramic has high toughness.

[0036] The zirconia ceramic provided by the present invention satisfies: light transmittance (800nm) ≤ 1.5%, preferably 0.5-1%. It can be seen that the zirconia ceramic has low light transmittance.

[0037] In the present invention, measuring the thinning speed of the zirconia ceramic can reflect the processability of the zirconia ceramic. Preferably, the zirconia ceramic satisfies: the thinning speed is ≥ 30 wires / h, preferably 31-45 wires / h. Among them, the faster the copper plate thinning speed is, the faster the processing speed is, the higher the efficiency is during production, and the lower the cost is. It can be seen that the zirconia ceramic can have good processability.

[0038] In the present invention, in the drop weight impact test result of the zirconia ceramic, the average drop weight height is ≥ 20 cm, preferably 20-30 cm. Therefore, it can be known that the zirconia ceramic can have high impact resistance.

[0039] In the present invention, unless otherwise specified, the hardness parameter and toughness parameter are measured using a hardness tester and an indentation method (diamond indenter, force 10 kg, test pressure time 15 s); the density parameter is measured using a drainage method; the dielectric constant parameter is measured using a network analyzer to test the material at 2 GHz; the transmittance parameter is measured using a Shimadzu spectrophotometer; the thinning speed parameter is measured using the dimensional speed under the copper grinding disc, such as a fixed time of 1 h, and the thickness difference before and after copper grinding is tested; the average drop hammer height parameter is measured using a drop hammer impact tester, the sample is placed on a platform, and a 60 g drop hammer is used to hit the center of the sample, starting from a height of 5 cm, if there is no crack, the height is increased by 5 cm each time until visible cracks appear on the sample, and the height value is recorded.

[0040] The zirconia ceramic provided by the present invention can have low hardness, low light transmittance, high impact resistance, high toughness, low dielectric constant and low density, while having better processability. According to the present invention, preferably, the zirconia ceramic also satisfies: density ≤5.15g / cm 3 , preferably 4.5-5.1g / cm 3 ; Dielectric constant ≤ 23, preferably 14-22.5; Hardness ≤ 1300Hv, preferably 1050-1290Hv; Toughness ≥ 4MPa·m 1 / 2 , preferably 4-6MPa·m 1 / 2 ; Transmittance (800nm) ≤1.5%, preferably 0.5-1%; Thinning speed ≥30 filaments / h, preferably 31-45 filaments / h; Average drop hammer height ≥20cm, preferably 20-30cm.

[0041] According to a particularly preferred embodiment of the present invention, based on the total amount of the zirconia ceramic, the zirconia ceramic contains, in terms of elements: 20.65-45.43wt% Zr, 0.61-3.43wt% Y, 4.53-29.83wt% Sr and 5.05-31.69wt% Al; and the zirconia ceramic includes: 30-63wt% tetragonal zirconia, 37-70wt% secondary phase and 0-0.5wt% monoclinic zirconia; the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconium oxide;

[0042] When the molar ratio α of Sr to Al satisfies: 1:12<α<1:2, the secondary phase contains SrAl 12 O 19 and SrAl2O4;

[0043] When the molar ratio of Sr to Al satisfies: α = 1:12, the secondary phase contains SrAl 12 O 19 ;

[0044] When the molar ratio α of Sr to Al satisfies: α=1:2, the secondary phase contains SrAl2O4.

[0045] The second aspect of the present invention provides a composition for preparing the zirconia ceramic provided in the first aspect, the composition comprising: zirconia powder, strontium oxide powder and aluminum oxide powder; wherein, based on the total amount of the zirconia powder, the zirconia powder contains 1.5-4 mol% of yttrium oxide.

[0046] In some embodiments of the present invention, preferably, the zirconium oxide powder contains yttrium oxide, has a median particle size of 0.3-0.6 μm, and a specific surface area of ​​7-13 m 2 / g; the median particle size of strontium oxide powder is 8-12μm; the median particle size of aluminum oxide powder is 0.15-0.6μm.

[0047] In the embodiment provided by the present invention, the above-mentioned composition contains the above-mentioned various oxide powders, and a zirconia ceramic with low hardness, low density, low light transmittance, high toughness, low light transmittance, high impact resistance and easy processing can be obtained. In the composition, the amount of each oxide powder used further preferably satisfies: based on the total amount of the composition, the content of the zirconium oxide powder is 30-63wt%, preferably 40-60wt%; the content of the strontium oxide powder is 5.35-35.27wt%, preferably 5.78-30.23wt%; the content of the aluminum oxide powder is 18.35-59.86wt%, preferably 19.83-51.31wt%. In the present invention, unless otherwise specified, the total amount of each oxide powder in the composition is 100wt%.

[0048] In the present invention, although the possible effects of the addition of various oxides can be considered, for example, yttrium oxide may stabilize and toughen zirconium oxide, aluminum oxide may have a reinforcing effect, and strontium oxide may aggregate with aluminum oxide to produce secondary phase particles (SrAl 12 O 19 and / or SrAl2O4), increase the impact resistance of the zirconia ceramic, and reduce the light transmittance, dielectric constant, hardness and density of the ceramic. However, when the zirconia ceramic provided by the present invention contains the above-mentioned specific contents of various elements and compositions, a zirconia ceramic with improved hardness can be obtained synergistically. When the contents of various oxides are not within the above-mentioned limited ranges, a zirconia ceramic that meets the performance of the present invention cannot be provided.

[0049] In some embodiments of the present invention, preferably, the molar ratio β of the strontium oxide powder and the aluminum oxide powder satisfies: 1:6≤β≤1:1, for example, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, and any value in the range of any two values. The present invention adopts the method of directly adding strontium oxide and aluminum oxide components to the composition, and strontium oxide and aluminum oxide are combined in a specific ratio to interact with each other. The secondary phase formed in the zirconia ceramic can improve the light transmittance and impact resistance of the ceramic, and at the same time make the ceramic have the characteristics of low density, low dielectric constant, low hardness, easy processing, etc.

[0050] A third aspect of the present invention provides a method for preparing a zirconia ceramic, the method comprising the following steps:

[0051] (1) mixing the powders in the composition provided in the second aspect with water, a dispersant and a binder and wet grinding them to obtain a slurry;

[0052] (2) drying the slurry to obtain composite zirconia ceramic powder;

[0053] (3) The composite zirconia ceramic powder is molded and sintered in sequence to obtain zirconia ceramic.

[0054] In the present invention, step (1) is to grind the various oxide powders used as raw materials to reduce the particle size and obtain a slurry; the grinding process is wet grinding, and the specific process may include: mixing the various oxide powders and water into a slurry, first ball milling and then sand milling, so that the median particle size of the various oxide powders reaches the nanometer level (such as 250-500nm).

[0055] In some specific embodiments of the present invention, the above-mentioned various oxide powders are ball-milled for 8-10 hours in a ball mill according to the content of the present invention, and then a dispersant and water are added to a sand mill for sand milling for 8-10 hours, and finally a binder in a suitable proportion is added and stirred for 2-4 hours. The ball mill and the sand mill use zirconia ceramic liners and zirconia grinding balls. The selected particle size of the zirconia grinding balls, the ratio of grinding balls with different particle sizes, the weight ratio of grinding balls to powders, and the amount of water can be controlled to achieve the desired particle size of the oxide powder.

[0056] In the present invention, the dispersant can promote uniform mixing of the components in the powder. Preferably, in step (1), the dispersant is selected from at least one of hydroxypropyl methylcellulose, sodium carboxymethyl cellulose and triethanolamine. In the present invention, the dispersant can be commercially available.

[0057] In the present invention, the binder is beneficial to the formability of the powder. Preferably, the binder is selected from polyvinyl alcohol and / or polyethylene glycol. Preferably, the binder is polyvinyl alcohol and polyethylene glycol. More preferably, the molar ratio of polyvinyl alcohol to polyethylene glycol is 1:1-2, preferably 1:1. Wherein, the average molecular weight of polyvinyl alcohol is 60000-200000 g / mol; the average molecular weight of polyethylene glycol is 2000-6000 g / mol. In the present invention, the binders are all commercially available.

[0058] In some embodiments of the present invention, preferably, in step (1), the weight ratio of the dispersant, the binder and the composition is 0.005-0.5:0.5-5:100, preferably 0.01-0.1:2-5:100.

[0059] In some embodiments of the present invention, preferably, the solid content of the slurry is 20-60wt%, for example, 20wt%, 25wt%, 30wt%, 40wt%, 50wt%, 55wt%, 60wt%, and any value in the range of any two values, preferably 25-55wt%. Such a setting is more conducive to the abrasive effect.

[0060] In the present invention, step (2) can adopt various drying methods, for example, spray drying can be adopted to form spherical powder with strong fluidity. Preferably, the inlet air temperature of the spray drying is 220-280°C, the outlet air temperature is 100-120°C, and the centrifugal speed is 10-20rpm.

[0061] According to the present invention, step (3) can be used to prepare composite zirconium oxide powder into ceramics. The composite zirconium oxide powder can be first molded and then sintered. Preferably, the molding method includes but is not limited to dry pressing, isostatic pressing, injection molding, and hot die casting. Dry pressing is preferred. A press with a tonnage of 180-200 tons can be used to use an oil pressure of 6-10MPa for molding, such as the shape of a mobile phone back cover.

[0062] According to the present invention, the sintering may be sintering in air. Preferably, in step (3), the sintering conditions include: a temperature of 1400-1600°C, preferably 1450-1550°C; and a sintering time of 1-5h, preferably 1-2h.

[0063] In the present invention, the ceramic obtained by sintering is also subjected to flat grinding and polishing, and then cut into a final product using a laser.

[0064] The fourth aspect of the present invention provides an electronic product housing, wherein the electronic product housing comprises the zirconium oxide ceramic provided in the first aspect. In the present invention, the electronic product housing includes but is not limited to a mobile phone back shell.

[0065] The present invention will be described in detail below by way of examples. In the following examples and comparative examples, the fracture toughness K ic : Hardness tester indentation method (diamond indenter, force 10kg, test time 15s);

[0066] Hardness Hv: hardness tester and indentation method (diamond indenter, force 10kg, test time 15s);

[0067] Processability: The speed of the copper grinding disc under the dimensional test, for example, the fixed time is 1h, and the thickness difference before and after the copper grinding is tested, which is recorded as the thinning speed, wire / h;

[0068] Density: The average number of pits (greater than 20 μm) within a range of 10×10 mm on the large surface of the polished sample;

[0069] Drop hammer impact: Use a drop hammer impact tester (manufacturer CKSI, model E602SS), place the sample on the platform, and use a 60g drop hammer to hit the center of the sample, starting from a height of 5cm. If there is no crack, increase the height by 5cm each time until visible cracks appear on the sample, and record the height value;

[0070] Light transmittance: tested using Shimadzu spectrophotometer;

[0071] Dielectric constant: Use a network analyzer to test the dielectric constant of the material at 2GHz;

[0072] Density parameters were measured using the displacement method;

[0073] XRD test: Use X-ray diffractometer Smartlab (3kW) to test the phase type and content;

[0074] XRF detection: Energy dispersive X-ray fluorescence spectrometer EDX-7000 was used to test the element content of the polished samples.

[0075] In the following examples and comparative examples, the composition and dosage of the raw materials and the prepared samples are shown in Table 1.

[0076] Example 1

[0077] Raw materials: 200g of composite powder, which contains 16.24wt% of strontium oxide (SrO), 33.76wt% of aluminum oxide (Al2O3), and 50wt% of zirconium oxide powder containing 3mol% of yttria; wherein the molar ratio β of strontium oxide powder to aluminum oxide powder is 1:2.1;

[0078] The raw materials were ball-milled in a ball mill for 8 h with water, and then 0.02 wt% of sodium carboxymethyl cellulose and water were added to a sand mill and sand-milled for 10 h. Finally, 4 wt% of a binder (PEG 4000 and PVA at a molar ratio of 1:1) was added to the composite powder and stirred for 0.5 h to form a spray slurry with a solid content of 25 wt%;

[0079] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, centrifugal speed is 15rpm) to form a spherical powder with strong fluidity for dry pressing, and then dry pressed (a 200-ton press uses an oil pressure of 8MPa);

[0080] The molded powder was sintered at 1450° C. for 2 h, and the sintered product was polished and laser cut to produce zirconia ceramic S1.

[0081] The obtained zirconia ceramic S1 was subjected to high energy XRF and XRD tests. The results are shown in Table 1, where the molar ratio of Sr to Al is 1:4.2. Among them, the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconia; the secondary phase is SrAl 12 O 19 and SrAl2O4.

[0082] Example 2

[0083] Raw materials: 200g of composite powder, comprising 12.99wt% of strontium oxide (SrO), 27.01wt% of aluminum oxide (Al2O3), and 60wt% of zirconium oxide powder containing 3mol% of yttria; wherein the molar ratio β of strontium oxide powder to aluminum oxide powder is 1:2.1;

[0084] The raw materials were ball-milled in a ball mill for 8 h with water, and then 0.02 wt% of sodium carboxymethyl cellulose and water were added to a sand mill and sand-milled for 10 h. Finally, 4 wt% of a binder (PEG 4000 and PVA at a molar ratio of 1:1) was added to the composite powder and stirred for 0.5 h to form a spray slurry with a solid content of 25 wt%;

[0085] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, centrifugal speed is 15rpm) to form a spherical powder with strong fluidity for dry pressing, and then dry pressed (a 200-ton press uses an oil pressure of 8MPa);

[0086] The molded powder was sintered at 1450° C. for 2 h, and the sintered product was polished and laser cut to produce zirconia ceramic S2.

[0087] The obtained zirconia ceramic S2 was subjected to high energy XRF and XRD tests. The results are shown in Table 1, where the molar ratio of Sr to Al is 1:4.2. Among them, the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconia; the secondary phase is SrAl 12 O 19 and SrAl2O4.

[0088] Example 3

[0089] Raw materials: 200g of composite powder, which contains 19.48wt% of strontium oxide (SrO), 40.52wt% of aluminum oxide (Al2O3), and 40wt% of zirconium oxide powder containing 3mol% of yttria; wherein the molar ratio β of strontium oxide powder to aluminum oxide powder is 1:2.1;

[0090] The raw materials were ball-milled in a ball mill for 8 h with water, and then 0.02 wt% of sodium carboxymethyl cellulose and water were added to a sand mill and sand-milled for 10 h. Finally, 4 wt% of a binder (PEG 4000 and PVA at a molar ratio of 1:1) was added to the composite powder and stirred for 0.5 h to form a spray slurry with a solid content of 25 wt%;

[0091] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, centrifugal speed is 15rpm) to form a spherical powder with strong fluidity for dry pressing, and then dry pressed (a 200-ton press uses an oil pressure of 8MPa);

[0092] The molded powder was sintered at 1450° C. for 2 h, and the sintered product was polished and laser cut to produce zirconia ceramic S3.

[0093] The obtained zirconia ceramic S3 was subjected to high energy XRF and XRD tests. The results are shown in Table 1, where the molar ratio of Sr to Al is 1:4.2. Among them, the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconia; the secondary phase is SrAl 12 O 19 and SrAl2O4.

[0094] Example 4

[0095] Raw materials: 200g of composite powder, which contains 7.25wt% of strontium oxide (SrO), 42.75wt% of aluminum oxide (Al2O3), and 50wt% of zirconium oxide powder containing 3mol% of yttria; wherein the molar ratio β of strontium oxide powder to aluminum oxide powder is 1:6;

[0096] The raw materials were ball-milled in a ball mill for 8 h with water, and then 0.02 wt% of the composite powder of hydroxypropyl methylcellulose and water were added to a sand mill and sand-milled for 10 h. Finally, 4 wt% of the composite powder of the binder (PEG 4000 and PVA in a molar ratio of 1:1) was added and stirred for 0.5 h to form a spray slurry with a solid content of 25 wt%;

[0097] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, centrifugal speed is 15rpm) to form a spherical powder with strong fluidity for dry pressing, and then dry pressed (a 200-ton press uses an oil pressure of 8MPa);

[0098] The molded powder was sintered at 1450° C. for 2 h, and the sintered product was polished and laser cut to produce zirconia ceramic S4.

[0099] The obtained zirconia ceramic S4 was subjected to high energy XRF and XRD tests. The results are shown in Table 1, where the molar ratio of Sr to Al is 1:12. The tetragonal zirconia phase is a solid solution of yttrium oxide and zirconia; the secondary phase is SrAl 12 O 19 .

[0100] Example 5

[0101] Raw materials: 200g of composite powder, which contains 5.8wt% of strontium oxide (SrO), 34.2wt% of aluminum oxide (Al2O3), and 60wt% of zirconium oxide powder containing 3mol% of yttria; wherein the molar ratio β of strontium oxide powder to aluminum oxide powder is 1:6;

[0102] The raw materials were ball-milled in a ball mill for 8 h with water, and then 0.02 wt% of the composite powder of hydroxypropyl methylcellulose and water were added to a sand mill and sand-milled for 10 h. Finally, 4 wt% of the composite powder of the binder (PEG 4000 and PVA in a molar ratio of 1:1) was added and stirred for 0.5 h to form a spray slurry with a solid content of 25 wt%;

[0103] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, centrifugal speed is 15rpm) to form a spherical powder with strong fluidity for dry pressing, and then dry pressed (a 200-ton press uses an oil pressure of 8MPa);

[0104] The molded powder was sintered at 1450° C. for 2 h, and the sintered product was polished and laser cut to produce zirconia ceramic S5.

[0105] The obtained zirconia ceramic S5 was subjected to high energy XRF and XRD tests. The results are shown in Table 1, where the molar ratio of Sr to Al is 1:12. Among them, the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconia; the secondary phase is SrAl 12 O 19 .

[0106] Example 6

[0107] Raw materials: 200g of composite powder, which contains 8.7wt% of strontium oxide (SrO), 51.3wt% of aluminum oxide (Al2O3), and 40wt% of zirconium oxide powder containing 3mol% of yttria; wherein the molar ratio β of strontium oxide powder to aluminum oxide powder is 1:6;

[0108] The raw materials were ball-milled in a ball mill for 8 h with water, and then 0.02 wt% of the composite powder of hydroxypropyl methylcellulose and water were added to a sand mill and sand-milled for 10 h. Finally, 4 wt% of the composite powder of the binder (PEG 4000 and PVA in a molar ratio of 1:1) was added and stirred for 0.5 h to form a spray slurry with a solid content of 25 wt%;

[0109] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, centrifugal speed is 15rpm) to form a spherical powder with strong fluidity for dry pressing, and then dry pressed (a 200-ton press uses an oil pressure of 8MPa);

[0110] The molded powder was sintered at 1550°C for 2 hours, and the sintered product was polished and laser cut to produce zirconia ceramic S6.

[0111] The obtained zirconia ceramic S6 was subjected to high energy XRF and XRD tests. The results are shown in Table 1, where the molar ratio of Sr to Al is 1:12. Among them, the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconia; the secondary phase is SrAl 12 O 19 .

[0112] Example 7

[0113] The method of Example 1 is followed, except that the raw materials are different, that is, 200 g of composite powder, which contains 25wt% strontium oxide (SrO), 40wt% aluminum oxide (Al2O3), and 35wt% zirconium oxide powder containing 3mol% yttria, wherein the molar ratio β of strontium oxide powder to aluminum oxide powder is 1:1.6; other conditions are the same, and zirconium oxide ceramic S7 is obtained.

[0114] The obtained zirconia ceramic S7 was subjected to high energy XRF and XRD tests, and the results are shown in Table 1. The molar ratio of Sr to Al is 1:3.2. The tetragonal zirconia is a solid solution of yttrium oxide and zirconia; the secondary phase is SrAl 12 O 19 and SrAl2O4.

[0115] Example 8

[0116] Raw materials: 200g of composite powder, which contains 20wt% of strontium oxide (SrO), 20wt% of aluminum oxide (Al2O3), and 60wt% of zirconium oxide powder containing 3mol% of yttria; wherein the molar ratio β of strontium oxide powder to aluminum oxide powder is 1:1;

[0117] The raw materials were ball-milled in a ball mill for 8 h with water, and then 0.02 wt% of the composite powder of hydroxypropyl methylcellulose and water were added to a sand mill and sand-milled for 10 h. Finally, 4 wt% of the composite powder of the binder (PEG 4000 and PVA in a molar ratio of 1:1) was added and stirred for 0.5 h to form a spray slurry with a solid content of 25 wt%;

[0118] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, centrifugal speed is 15rpm) to form a spherical powder with strong fluidity for dry pressing, and then dry pressed (a 200-ton press uses an oil pressure of 8MPa);

[0119] The molded powder was sintered at 1400°C for 2 hours, and the sintered product was polished and laser cut to produce zirconia ceramic S8.

[0120] The obtained zirconia ceramic S8 was subjected to high energy XRF and XRD tests, and the results are shown in Table 1, where the molar ratio α of Sr to Al is 1:2. The tetragonal zirconia phase is a solid solution formed by yttrium oxide and zirconium oxide; the secondary phase is SrAl2O4.

[0121] Comparative Example 1

[0122] Raw materials: 200 g of composite powder, including 50 wt% of aluminum oxide (Al2O3) and 50 wt% of zirconium oxide powder containing 3 mol% of yttria.

[0123] The raw materials were ball-milled in a ball mill for 8 h with water, and then 0.02 wt% of sodium carboxymethyl cellulose and water were added to a sand mill and sand-milled for 10 h. Finally, 4 wt% of a binder (PEG 4000 and PVA at a molar ratio of 1:1) was added to the composite powder and stirred for 0.5 h to form a spray slurry with a solid content of 25 wt%;

[0124] The slurry is sent to a spray tower for spray drying (inlet air temperature is 250°C, outlet air temperature is 110°C, centrifugal speed is 15rpm) to form a spherical powder with strong fluidity for dry pressing, and then dry pressed (a 200-ton press uses an oil pressure of 8MPa);

[0125] The molded powder was sintered at 1450°C for 2 hours, and the sintered product was polished and laser cut to produce zirconia ceramic D1.

[0126] The obtained zirconia ceramic D1 was subjected to high energy XRF and XRD tests, and the results are shown in Table 1. Among them, the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconium oxide.

[0127] Comparative Example 2

[0128] The method of Comparative Example 1 is followed, except that the raw materials are different, that is, 200 g of composite powder, which contains 100 wt % of zirconium oxide powder containing 3 mol % of yttria, and other conditions are the same, to obtain zirconium oxide ceramic D2.

[0129] The obtained zirconia ceramic D2 was subjected to high energy XRF and XRD tests, and the results are shown in Table 1. Among them, the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconium oxide.

[0130] Comparative Example 3

[0131] The method of Comparative Example 1 is followed, except that the raw materials are different, i.e., 200 g of composite powder, which contains 10 wt% of strontium oxide (SrO), 60 wt% of aluminum oxide (Al2O3), and 30 wt% of zirconium oxide powder containing 3 mol% of yttrium oxide, wherein the molar ratio β of strontium oxide powder to aluminum oxide powder is 1:6, and other conditions are the same, to obtain zirconium oxide ceramic D3.

[0132] The obtained zirconia ceramic D3 was subjected to high energy XRF and XRD tests, and the results are shown in Table 1. Among them, the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconium oxide.

[0133] Comparative Example 4

[0134] The method of Example 1 is followed, except that the raw materials are different, that is, 200 g of composite powder, which contains 30wt% strontium oxide (SrO), 60wt% aluminum oxide (Al2O3), and 10wt% of zirconium oxide powder containing 3mol% yttria, wherein the molar ratio β of strontium oxide powder to aluminum oxide powder is 1:2, and other conditions are the same, to obtain zirconium oxide ceramic D4.

[0135] The obtained zirconia ceramic D4 was subjected to high energy XRF and XRD tests, and the results are shown in Table 1. Among them, the tetragonal zirconia is a solid solution formed by yttrium oxide and zirconium oxide.

[0136] Table 1

[0137]

[0138]

[0139]

[0140] Test Example 1

[0141] The samples prepared in Examples 1-8 and Comparative Examples 1-4 were tested for hardness, toughness, density and light transmittance. The results are shown in Table 2.

[0142] Table 2

[0143] Hardness, Hv <![CDATA[Toughness, MPa·m 1 / 2 > Number of pit points, Transmittance (800nm), % Example 1 1182 4.6 0 0.8 Example 2 1261 5.4 0 1 Example 3 1153 4.5 0 0.6 Example 4 1131 4.3 0 0.7 Example 5 1289 5.1 0 0.9 Example 6 1090 4.1 0 0.7 Example 7 1051 5.9 0 0.5 Example 8 1233 5.6 0 1.1 Comparative Example 1 1605 4.1 0 0.8 Comparative Example 2 1311 5.9 0 20.1 Comparative Example 3 1201 4.5 0 0.4 Comparative Example 4 1044 5.5 0 0.2

[0144] It can be seen from the data in Table 2 that, compared with Comparative Examples 1-4, the zirconia ceramic provided by the present invention has low hardness, high toughness, high density and low transmittance. In particular, by adjusting the content of each powder in the composition within the preferred protection range, the element and composition content of the zirconia ceramic is also within the preferred protection range, and the hardness, toughness and transmittance of the zirconia ceramic are further optimized.

[0145] It can be seen from Examples 1-3 that when the molar ratio α of Sr to Al in the zirconia ceramic is the same, the higher the total content of Sr and Al, the lower the hardness, toughness and light transmittance of the obtained zirconia ceramic.

[0146] Similarly, it can be seen from Examples 4-6 that when the molar ratio α of Sr to Al in the zirconia ceramic is the same, the higher the total content of Sr and Al, the lower the hardness, toughness and light transmittance of the obtained zirconia ceramic.

[0147] Test Example 2

[0148] The samples prepared in Examples 1-8 and Comparative Examples 1-4 were subjected to dielectric constant, density, processability, and drop hammer impact tests. The results are shown in Table 3.

[0149] Table 3

[0150] Dielectric constant <![CDATA[Density, g / cm 3 > Thinning speed, wire / h Average drop height, cm Example 1 18.7 4.83 37 24 Example 2 22.3 5.09 41 26 Example 3 15.4 4.68 34 21 Example 4 18.3 4.83 35 25 Example 5 21.8 5.03 39 28 Example 6 14.9 4.62 32 22 Example 7 14.3 4.76 39 20 Example 8 22.9 5.13 43 25 Comparative Example 1 17.8 4.75 9 15 Comparative Example 2 36.1 6.06 47 31 Comparative Example 3 13.6 4.61 23 18 Comparative Example 4 13.1 4.51 22 17

[0151] Compared with comparative examples 1-4, the zirconia ceramics provided by the present invention simultaneously meet the following requirements: dielectric constant ≤ 23, density ≤ 5.15 g / cm 3 , thinning speed ≥ 30 wires / h, average drop weight height ≥ 20 cm, that is, compared with comparative examples 1-4, the zirconia ceramics provided by the present invention simultaneously meet the advantages of low dielectric constant, low density, high impact resistance and easy processing.

[0152] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A zirconia ceramic, characterized in that: Based on the total amount of the zirconia ceramic, the zirconia ceramic contains, in terms of elements, 20.65-45.43wt% of Zr, 0.61-3.43wt% of Y, 4.53-29.83wt% of Sr and 5.05-31.69wt% of Al; and the zirconia ceramic includes: 30-63wt% of tetragonal zirconia and 37-70wt% of a secondary phase, and the secondary phase contains SrAl 12 O 19 and SrAl2O4; the tetragonal zirconia is a solid solution of yttrium oxide and zirconium oxide; Among them, in the zirconia ceramic, SrAl 12 O 19 Existing in the form of whiskers and SrAl 12 O 19 The aspect ratio of the whiskers is ≥4:1, and SrAl2O4 exists in the form of spinel.

2. The zirconia ceramic according to claim 1, wherein Based on the total amount of the zirconia ceramic, the zirconia ceramic comprises, in terms of elements: 27.53-43.26 wt % of Zr, 0.81-3.27 wt % of Y, 4.88-25.56 wt % of Sr and 10.49-27.16 wt % of Al; The zirconia ceramic comprises: 40-60wt% of tetragonal zirconia and 40-60wt% of secondary phase.

3. The zirconia ceramic according to claim 1 or 2, wherein: The zirconia ceramic meets the following requirements: hardness ≤ 1300 Hv.

4. The zirconia ceramic according to claim 3, wherein: The zirconia ceramic meets the following requirements: hardness is 1050-1290 Hv.

5. The zirconia ceramic according to claim 1 or 4, wherein: The zirconia ceramic meets the following requirements: density ≤ 5.15 g / cm 3 .

6. The zirconia ceramic according to claim 5, wherein: The zirconia ceramics satisfy the following requirements: density is 4.5-5.1 g / cm 3 .

7. The zirconia ceramic according to claim 1 or 6, wherein: The zirconium oxide ceramic satisfies: a dielectric constant ≤ 23.

8. The zirconia ceramic according to claim 7, wherein: The zirconium oxide ceramics satisfy the following requirements: a dielectric constant of 14-22.

5.

9. The zirconia ceramic according to claim 1 or 8, wherein: The zirconia ceramics meet the following requirements: toughness ≥ 4 MPa·m 1 / 2 .

10. The zirconia ceramic according to claim 9, wherein: The zirconia ceramics meet the following requirements: toughness is 4-6 MPa·m 1 / 2 .

11. The zirconia ceramic according to claim 1 or 10, wherein: The zirconium oxide ceramic meets the following requirements: 800nm ​​light transmittance ≤1.5%.

12. The zirconia ceramic according to claim 11, wherein: The zirconium oxide ceramic meets the following requirements: the light transmittance at 800nm ​​is 0.5-1%.

13. The zirconia ceramic according to claim 1 or 12, wherein: The zirconia ceramic meets the following requirements: a thinning rate of ≥30 wires / h.

14. The zirconia ceramic according to claim 13, wherein: The zirconia ceramic meets the requirement that the thinning speed is 31-45 wires / h.

15. The zirconia ceramic according to claim 1 or 14, wherein: The zirconia ceramic meets the requirement that the average drop height is ≥ 20 cm.

16. The zirconia ceramic according to claim 15, wherein: The zirconia ceramics satisfy: an average drop height of 20-30 cm.

17. The method for preparing the zirconium oxide ceramic according to any one of claims 1 to 16, characterized in that: The method comprises the following steps: (1) mixing zirconium oxide powder, strontium oxide powder, aluminum oxide powder, water, a dispersant and a binder and wet grinding to obtain a slurry, wherein the zirconium oxide powder contains 1.5-4 mol% of yttrium oxide based on the total amount of the zirconium oxide powder; Based on the total amount of the zirconium oxide powder, the strontium oxide powder and the aluminum oxide powder, the content of the zirconium oxide powder is 30-63wt%; the content of the strontium oxide powder is 5.35-35.27wt%; the content of the aluminum oxide powder is 18.35-59.86wt%; (2) drying the slurry to obtain composite zirconia ceramic powder; (3) The composite zirconia ceramic powder is molded and sintered in sequence to obtain zirconia ceramic.

18. The method according to claim 17, wherein: In step (1), based on the total amount of the zirconium oxide powder, the strontium oxide powder and the aluminum oxide powder, the content of the zirconium oxide powder is 40-60wt%; the content of the strontium oxide powder is 5.78-30.23wt%; and the content of the aluminum oxide powder is 19.83-51.31wt%.

19. The method according to claim 17 or 18, wherein: In step (1), the molar ratio β of the strontium oxide powder and the aluminum oxide powder satisfies: 1:6≤β≤1:

1.

20. The method according to claim 19, wherein: In step (1), the weight ratio of the dispersant, the binder and the total weight of the zirconium oxide powder, the strontium oxide powder and the aluminum oxide powder is 0.005-0.5:0.5-5:

100.

21. The method according to claim 17 or 20, wherein: In step (1), the weight ratio of the dispersant, the binder and the total weight of the zirconium oxide powder, the strontium oxide powder and the aluminum oxide powder is 0.01-0.1:2-5:

100.

22. The method according to claim 21, wherein: In step (1), the dispersant is selected from at least one of hydroxypropyl methylcellulose, sodium carboxymethyl cellulose and triethanolamine; and the binder is selected from polyvinyl alcohol and / or polyethylene glycol.

23. The method according to claim 19, wherein: In step (1), the solid content of the slurry is 20-60wt%.

24. The method according to claim 23, wherein: In step (1), the solid content of the slurry is 25-55wt%.

25. The method of claim 17, wherein: In step (3), the sintering conditions include: temperature of 1400-1600° C. and time of 1-5 h.

26. The method according to claim 25, wherein: In step (3), the sintering conditions include: temperature of 1450-1550°C and time of 1-2h.

27. An electronic product housing, characterized in that: The electronic product housing contains the zirconium oxide ceramic according to any one of claims 1 to 16.

Citation Information

Patent Citations

  • Thermal shock-resistant composite materials

    CN108349817A

  • Ceramics with high toughness, strength and hardness

    US5002911A